The effect of a dual or a triple antithrombotic therapy with apixaban on thrombus formation in vivo and in an ex vivo perfusion chamber model: An open-label, controlled, sequential study. Issue 27 (July 2016) - Weisshaar, Stefan; Litschauer, Brigitte; Bucher, Sebastian; Riesenhuber, Martin; Kapiotis, Stylianos; Kyrle, Paul Alexander; Wolzt, Michael
Abstract: Background: There is a need to optimize pharmacological treatment in patients with acute coronary syndrome and concomitant atrial fibrillation, in particular with newer antithrombotic medicines. We have therefore studied if dual or triple combination of antithrombotic agents exert similar effects on coagulation activation in an in vivo model in the skin microvasculature and in an ex vivo perfusion chamber. Methods and Results: Shed blood platelet activation (β-thromboglobulin [β-TG]), thrombin generation (thrombin-antithrombin complex [TAT]) and volume as well as markers of thrombus size (D-dimer) and its platelet content (P-selectin) in a perfusion chamber were studied in a sequential, open-label, parallel group trial in 40 healthy male volunteers (n = 20 per group). Subjects received ticagrelor and apixaban without or with acetylsalicylic acid (ASA). Outcome parameters were assessed at 3 hours after therapy dosing, and at steady-state trough and peak conditions. A triple or dual therapy induced a comparable decrease in shed blood β-TG at 3 hours after therapy dosing but was more pronounced at steady-state conditions with the more intense treatment combination. During both antithrombotic regimens a similarly sustained inhibition in thrombin generation was observed which was accompanied by comparable increases in shed blood volume. In contrast, no treatment effect could be observed in the perfusion chamber experiment. Conclusion: Ticagrelor and apixaban with or without ASA inhibit platelet activation and thrombin formation in vivo in healthy subjects. Platelet inhibition was greater at steady-state conditions after triple therapy administration.